Efficacy and Safety of Blinatumomab in the Treatment of Acute Lymphoblastic Leukemia: Systematic Literature Review - Gonçalves, Renan do Nascimento (2024)
Introduction: The conventional treatment options for acute lymphoblastic leukemia (ALL) are chemotherapy, blood transfusion, and bone marrow transplant. Blinatumomab is a novel form of treatment that uses bispecific antibody technology to fight ALL. Objective: Systematic literature review to evaluate the efficacy and safety of blinatumomab for the treatment of patients with ALL. Method: Studies on the topic were searched in the Cochrane, Embase, LILACS and PubMed databases. The Rayyan and EndNote tools were used for reference management. The selection, extraction and quality assessment stages were conducted in pairs and disagreements were resolved by consensus. The quality of the evidence obtained and the risk of bias were assessed using Cochrane's GRADE and RoB 2 tools. Results: Five scientific articles referred to three multicenter and international randomized clinical trials were included for analysis. The results related to overall survival, progression-free survival and adverse events were better in the blinatumomab group compared with conventional chemotherapy. The analysis of risk of bias raised some concerns for the progression-free survival and adverse events outcomes, mainly due to the blinding of participants, which also determined that the degree of certainty of the evidence was classified as moderate. Conclusion: Increased survival and lower rate of adverse events were observed for the blinatumomab group, suggesting that it is more effective and safer when compared to conventional chemotherapy for the treatment of ALL.